The effect of whipping/springing on fatigue damage and extreme response of ship structures - Mao, Wengang; Ringsberg, Jonas; Rychlik, Igor (29th International Conference on Ocean, Offshore and Arctic Engineering: Volume 2, 2010)
Wave-induced vibrations, also known as whipping and springing, are defined as high frequency response of ship structures. In this paper, the fatigue damage caused by whipping and springing is presented by investigating the amidships section of a 2800 TEU container ship that operates in the North Atlantic Ocean. A simplified fatigue model, originally from the generalized narrow-band approximation for Gaussian load, is employed to include the damage contribution from wave-induced vibrations. In this model, the significant response range hs and the mean stress up-crossing frequency fz are simplified using only the wave-induced loading and encountered wave frequency, respectively. The capacity and accuracy of the model is illustrated by application on the measurements of the 2800 TEU container ship for different voyages during 2008. The whipping-induced contribution to the extreme response is investigated by means of the level crossing approach. It shows that the level crossing model for Gaussian load cannot be used for the prediction of extreme responses, such as the 100-year stress, based on a half-year full-scale measurement. It is found that a more complicated non-Gaussian model is required to consider the contribution from whipping.